Stroke Mortality Attributable to Low Fruit Intake in China: A Joinpoint and Age-Period-Cohort Analysis - Luo, Lisha; Jiang, Junfeng; Yu, Chuanhua; Zhao, Mingjuan; Wang, Yunyun; Li, Quanlei; Jin, Yinghui (Frontiers in Neuroscience, 2020)
Stroke is the first leading cause of death in China and low fruit intake is suggested to be one of the most important risk factors for stroke mortality. However, the trends of stroke mortality attributable to low fruit intake remain unclear in China. Therefore, this study aimed to investigate the long-term trends of stroke mortality attributable to low fruit intake by sex in China during 1990-2017. Data were obtained from Global Burden of Disease 2017 (GBD 2017) study, the annual percentage change (APC) and average annual percentage change (AAPC) were estimated by joinpoint regression analysis, and the net age, period, and cohort effects were estimated using age-period-cohort model with an intrinsic estimator algorithm (APC-IE). The crude mortality rates (CMRs) increased for males and decreased for females from 1990 to 2017. The age-standardized mortality rates (ASMRs) for both males and females showed consecutive significant declines from 1990 to 2017. By APC analysis, substantially increasing age effects were presented from 25 to 79 years for both sexes. The independent period and cohort effects progressively decreased during the entire period for both sexes, with a faster decrease for females than for males. Males and elder groups were the high-risk population for stroke mortality caused by low fruit intake. Although the mortality risk showed a decreasing trend, the fruit intake was still low for Chinese population. Therefore, effective strategies and global awareness are essential to improve the current situation of low fruit intake, thereby to prevent and reduce the stroke mortality risk caused by low fruit intake in China.